PENGELOLAAN RIPARIAN SUNGAI UNTUK PENANGANAN EROSI BERBASIS PARTISIPASI MASYARAKAT - Farida, Farida; Mandra, Moh. Ahsan S. (UNM Environmental Journals, 2023)
Indonesia is one of the countries that has started to develop organic farming. The Erosion is a very serious hazard that threatens anyone living along the riverbanks, although sometimes slowly, the consequences are enormous, including loss and loss of life, sedimentation and endangered river biota. River riparian management is an approach to protect and restore riparian ecological functions (areas around rivers) that are important for the sustainability of river ecosystems. The purpose of this study was to see how much influence community participation had on river riparian management for erosion control. The research was conducted by pretest and posttest analysis of increasing public knowledge by using paired sample t test. The results of the analysis show that there is an increase in knowledge before and after being given training on river riparian management for erosion management based on community participation. These results also indicate that the training provided to local communities is effective for use on a larger research scale.